Associated Factors of Postoperative Cognitive Dysfunction: A Literature Review - Tornsatitkul, Surapa (Thai Journal of Anesthesiology, 2021)
Postoperative Cognitive Dysfunction (POCD) is defined as declining of one or more discrete areas of mental state postoperatively. The pathogenesis is unclear, but the most possible is inflammatory process in the brain. There is no specific treatment. Hence, POCD prevention by adjusting risk and protective factors should be conducted. This literature review shows 3 groups of associated factors. First, patient risk factors are old age, low education level, history of anticholinergic or sedative drugs usage, neurological diseases, diabetes mellitus, renal disease, carrier of ApoE ε4 gene, delirium, Systemic Inflammatory Response Syndrome and anemia. Second, anesthetic risk factors are benzodiazepine and high amount of opioid usage. Anesthetic protective factors are the usage of dexmedetomidine, ketamine, parecoxib, monitoring depth of anesthesia, patient-controlled epidural analgesia, and peripheral nerve block. Third, surgical risk factors are cardiac surgery, major surgery, long duration of surgery, blood loss and long waiting time before surgery. Previous studies have shown that these factors contributed differently to POCD, but the results were mostly modest. These studies are heterogeneity due to lack of definite diagnosis criteria of POCD. The further large and welldesigned studies are needed to confirm this association.